Opportunities and Challenges of Generic Pre-Exposure Prophylaxis Drugs for HIV. (2022) - Ballreich, Jeromie; Levengood, Timothy; Conti, Rena M.
Abstract: Antiretroviral pre-exposure prophylaxis (PrEP) is protective against HIV. Low utilization rates amongst HIV vulnerable populations are due in part to the high cost of PrEP. Generic PrEP offers the potential to improve health at significantly reduced costs. In this study, we examine early utilization patterns and prices for generic PrEP. We discuss the opportunities and challenges for generic PrEP to improve health among HIV vulnerable populations.